The Mediating Role of Place Attachment Dimensions in the Relationship Between Local Social Identity and Well-Being - Maricchiolo, Fridanna; Mosca, Oriana; Paolini, Daniele; Fornara, Ferdinando (Frontiers in Psychology, 2021)
Well-functioning communities provide a range of material and psychological resources that enhance well-being. The degree to which individuals see themselves as part of the local social group, or Local Social Identity, i.e. the social identification with the community of the place where people are living, may play an important role in enhancing happiness and well-being, as well as people’s relationships with their own living environment, i.e. Place Attachment. We hypothesized that Local Social Identity influences well-being via specific components of Place Attachment to the residential city/town, i.e. Place Identity, Social Relations and Lack of Resources (which is the opposite of Place Dependence). We measured Local Social Identity, Individual Well-being, Interdependent Happiness and Place Attachment in a sample of N = 375 participants. We tested our hypotheses conducting a series of mediation analyses with Local Social Identity as IV, Individual Well-being and Interdependent Happiness as DVs and Place Attachment sub-factors, i.e. Place Identity, Social Relations and Lack of Resources, as mediators. Results showed that the relation between Local Social Identity and both Individual Well-being and Interdependent Happiness was positively mediated by Place Identity and Social Relations, while the Lack of Resources emerged as a negative mediator only in the relation between Local Social Identity and Individual Well-being (not for Interdependent Happiness). Practical implications and future developments are discussed.